Pressure evolution of electrical transport in the 3D topological insulator (Bi, Sb)2(Se, Te)3. (18th March 2015) - Jeffries, J R; Butch, N P; Vohra, Y K; Weir, S T
Abstract: The group V-VI compounds—like Bi2 Se3, Sb2 Te3, or Bi2 Te3 —have been widely studied in recent years for their bulk topological properties. The high-Z members of this series form with the same crystal structure, and are therefore amenable to isostructural substitution studies. It is possible to tune the Bi-Sb and Te-Se ratios such that the material exhibits insulating behavior, thus providing an excellent platform for understanding how a topological insulator evolves with applied pressure. We report our observations of the pressure-dependent electrical transport and crystal structure of a pseudobinary (Bi, Sb)2 (Te, Se)3 compound. Similar to some of its sister compounds, the (Bi, Sb)2 (Te, Se)3 pseudobinary compound undergoes multiple, pressure-induced phase transformations that result in metallization, the onset of a close-packed crystal structure, and the development of distinct superconducting phases.